Kadar estradiol serum pada wanita menopause dengan dan tanpa sindroma vasomotor di RSUP H Adam Malik dan RS Jejaring Fakultas Kedokteran Universitas Sumatera Utara Medan - Tri Sugeng Hariadi; M. Fidel Ganis Siregar; Hanudse Hartono; Makmur Sitepu; M. Rhiza Z. Tala; Cut Adeya Adella (Majalah Kedokteran Nusantara The Journal Of Medical School, 2014)
Background: Physiologic changes from the reproductive to non reproductive phase is characterized by a gradual decline in estrogen levels. In menopausal women decline of estrogen levels can causes various complaints, one of which is the vasomotor syndromeAim: This study was conducted to determine estradiol serum levels in menopausal women with and without vasomotor syndrome and estradiol serum levels in menopausal women based on severity degrees (mild, moderate, and severe).Metode: This analytical cross sectional study involved 60 women, 34 women with vasomotor syndrome and 26 women with non vasomotor syndrome. Serum estradiol levels in every groups were checked. Data were statistically analysed using Anova and Spearmen correlation tests (p<0.05; CI 95%).Results : Non vasomotor syndrome estradiol serum mean rank was significantly higher than vasomotor syndrome estradiol serum mean rank (17.5 vs 47,5 pg/mL). Mean estradiol levels of menopausal vasomotor syndrome subjects based on severity degrees for mild, moderate, and severe degrees are 25.80 ± 2.34 pg/ml; 15.58 ± 2.64 pg/ml; and 11,80 pg/ml (P<0.05). Age, menopausal age, and menopausal length was significantly negatively correlated with estradiol levels with r values of -0.859, - 0.830, and -0.880, respectively. Body Mass Index (BMI) was significantly positively correlated with estradiol levels with a r value of 0.699Conclusion: Serum estradiol levels were lower in vasomotor syndrome women than non vasomotor women. There is significantly differed serum estradiol levels based on severity degress. More severe degrees of vasomotor syndrome will make lowerv serum estradiol levels. Subject characteristics were also significantly associated with serum estradiol levels in menopausal women. Key Words : Menopause, vasomotor syndrome, serum estradiol.